Caracterização físico-química, biometria e perfil volátil do murici (byrsonima crassifólia sp.). - SILVA, Wanderson Rodrigues da. (Universidade Federal do Tocantins, 2024)
The muricizeiro was first described by the Swedish botanist Carolus Linnaeus in 1753 as Malpighia crassifolia L. In 1821, the botanist Karl Sigismund Kunth, recognizing the impropriety of placing the species in the genus Malpighia, proposed a new combination, naming it Byrsonima crassifolia (L.) Kunth. The plant has a fruit known as murici, much appreciated in Brazil, especially in cooking, due to its exotic flavor and for being rich in nutrients and for having a characteristic aroma, described as cheesy, fruity and floral notes, encompassing diverse chemical class. Due to these characteristics, murici is consumed in natura, in the form of preserves, jellies, sweets, liqueurs, mousse, juices and ice creams, it is also important for our body in the supply of dietary fiber and vitamin C. The fruits of our work were harvested in an open area, in the Vitória Régia settlement, municipality of Aragominas – TO and analyzed according to their physicochemical characteristics with mean values found for length (15 mm), diameter (15.53 mm), weight (3.21 g), pH (3.38), total titratable acidity (1.28%), moisture (72.53%), ash (1.54%) and °Brix (5.10). The results showed that murici is composed mostly of esters and ketones, thus characterizing its fruity aroma and cheese characteristics, which makes its flavor exotic.